Brucellosis-related acute pancreatitis: A rare complication of a universal disease. (February 2016) - Suvak, Burak; Dulger, Ahmet Cumhur; Karadas, Sevdegul; Gonullu, Hayriye; Bayram, Yasemin; Gonullu, Edip; Batur, Abdussamet; Aykaç, Mehmet Coşkun; Gunduz, Ali Mahir; Aytemiz, Enver; Guducuoglu, Huseyin
Objectives: To determine the prevalence and determinants of acute pancreatitis in patients with acute brucellosis. Methods: Adult patients with brucellosis were retrospectively recruited. Brucellosis and acute pancreatitis were diagnosed according to standard criteria. Laboratory analyses included Wright agglutination titre, serum biochemical parameters and blood count. Results: Patients with acute pancreatitis ( n = 21) had significantly higher Wright agglutination titres, alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, γ-glutamyl transpeptidase, amylase, lipase and serum glucose concentrations, and significantly lower haemoglobin concentrations and haematocrit than patients with brucellosis alone ( n = 326). Conclusions: Hyperglycaemia, anaemia, and liver transaminase and cholestatic enzyme concentrations may represent new approaches for assessing disease severity in patients with brucellosis and acute pancreatitis.